Conceptual Model for the Generation of Performance Measures in Manufacturing Firms - Quezada, Luis E.; O’Brien, Christopher; Córdova, F.; Palominos, P. (Brazilian Journal of Operations & Production Management, 2010)
This paper shows a conceptual model for the generation of performance measures in manufacturing fi rms. The conceptual model is based on a hierarchical approach for formulating manufacturing strategies in small and medium enterprises, which structures the process as a hierarchy and links the levels using tools of the Analytic Hierarchy Process (AHP). The original model consists of 4 levels: (a) the well-being of the company, (b) strategic objectives, (c) strategic business units, (c) critical success factors and (d) manufacturing decision area. This model includes the four perspectives of the Balanced Scorecard, as follows. The fi nancial perspective is included in the strategic objectives, the customer perspective is included in the critical success factors and the process perspective and innovation & development perspective are included in the manufacturing decision areas. In this way, the same hierarchical model for formulating a manufacturing strategy can be used as a tool for generating performance measures. The main contribution of this work is that it provides with a systematic mechanism for generating performance measures. It also allows the assignation of weights to the measures created, using a well known and proved process as AHP.